Peran Electronic Word of Mouth (e-WOM) dan E-Service Quality terhadap Customer Engagement Mahasiswa Kewirausahaan UPI Tasikmalaya - Mulyani, Ira Adinda Sri; Sujaya, Krisna; Fauziyah, Azizah (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The fast advancement of digital technologies and social media has changed how higher education facilitates communication and interaction. The research aims to study how Electronic Word of Mouth (e-WOM) and E-Service Quality affect and have a role in improving Customer Engagement in particular in entrepreneurship students at the University of Education Indonesia (UPI) Campus Tasikmalaya. The research is conducted using a quantitative approach, data is collected with surveys through the dissemination of questionnaires to active entrepreneurship students at UPI Tasikmalaya which are analyzed with descriptive and verification analysis. With a 5% error rate using Slovin formula, 168 students from the 2020-2023 were the samples of the research. Data processing is facilitated by the software tool SPSS v.26 to test the hypothesis. The findings showed revealed that e-WOM and e-service quality had a partial and simultaneous impact of 78.4% on @entre.upi Instagram customer engagement, with other factors affecting it such as brand equity and customer satisfaction influencing the remaining 21.6%. Therefore, it was found that colleges have an important role in improving and maintain student customer engagement through e-WOM and e-service quality. Pesatnya perkembangan teknologi digital dan media sosial mengubah lanskap perguruan tinggi memfasilitasi komunikasi dan interaksi. Penelitian memiliki tujuan untuk mengkaji bagaimana Electronic Word of Mouth (e-WOM) dan E-Service Quality mempengaruhi Customer Engagement khususnya pada mahasiswa kewirausahaan di Universitas Pendidikan Indonesia (UPI) Kampus Tasikmalaya. Penelitian dilakukan dengan pendekatan kuantitatif, data dikumpulkan dengan survei melalui penyebaran kuesioner kepada mahasiswa aktif kewirausahaan UPI Tasikmalaya yang dianalisis dengan analisis deskriptif dan verifikatif. Populasi dalam peneletian yaitu mahasiswa kewirausahaan sebanyak 290 mahasiswa yang berkuliah dari tahun akademik 2020-2023. Dengan tingkat kesalahan 5% menggunakan rumus slovin, 168 mahasiswa dari angkatan 2020-2023 menjadi sampel dari penelitian. Pengolahan data difasilitasi dengan alat perangkat lunak SPSS v.26 untuk menguji hipotesis. Hasilnya menunjukkan bahwa e-WOM dan e-service quality memberikan pengaruh secara parsial dan simultan sebesar 78,4% terhadap customer engagement Instagram @entre.upi dan sebesar 21,6% sisanya dipengaruhi faktor lain yang mempengaruhinya seperti ekuitas merek dan kepuasan pelanggan. Oleh karena itu, ditemukan bahwa perguruan tinggi memiliki peran penting dalam meningkatkan dan mempertahankan customer engagement mahasiswa melalui e-WOM dan e-service quality.